Avicelase Enzyme from Sawdust: Isolation, Production and Optimization - Makky, Essam A.; Noor Afifah, Fauzi (www.mutagens.co.in, 2014)
Economical disposal of sawdust is a problem of growing concern to the wood industries as waste. On an industry-wide basis most of sawdust is green and has many uses that able to be converted to useful products such as fuel, chemical feedstock or textiles. Cellulose is a potential substrate to the enzyme that can be produced from the activation of cellulose conversion into monomer. Using microorganisms such as bacteria and fungi as a converter, cellulose can be degraded and converted into reducing sugar with the help of various enzymes including Avicelase enzyme. The utilization of sawdust as a potential substrate for producing enzymes may serve a dual purpose of reducing the environmental pollution along with producing a high value commercial product. Effect of nutritional parameters such as initial pH, carbon and nitrogen sources for Avicelase production from Bacillus sp. was investigated. From three different sources of isolates, only one of the most potent isolate was selected from a food source CL5 which has been partially identified and suggested to be Bacillus species. Optimum pH-value, carbon and nitrogen sources for Avicelase production found to be 7.0, lactose and KNO3 were (2.450±0.009 IU/ml) increased up to 3556.7% with sp. act. 1.528 IU/mg; (1.286±0.074 IU/ml) increased up to 1548.7% with sp. act. 0.631 IU/mg and (2.287±0.109 IU/ml) increased to 3313.4% with sp. act. 0.979 IU/mg, respectively